Rancangan Skema Penilaian Kinerja yang saling Mendukung antara Individu dan Departemen: Studi Kasus Perusahaan Jasa Konstruksi - Ieneke Kathryn Kodrat; I Nyoman Sutapa (Jurnal Titra, 2021)
Company’s performance can be seen from the ability of it’s employees and departments to work well and achieve the targets set by the company. Performance appraisal as a basis for awarding in this company is currently only based on individual performance appraisal, namely the employee’s ability to complete the assigned task which causes employees to only care about the results of their work and less concerned about the achievement of the department and the company as a whole. The ability to work together and support each other in a department or company is one of the most important key to succeed in achieving existing goals. This research focuses on designing an improved performance appraisal scheme that includes the factor of cooperation between individuals within the department or company so that the assessment given is fair. The proposed improvement in the assessment scheme also describes a mutually supportive working relationship between individuals and departments in achieving company goals based on the company’s vision, mission, and quality objectives.